Microstructure evolution mechanisms and a physically-based constitutive model for an Al–Zn–Mg–Cu–Zr aluminum alloy during hot deformation - Daoguang He; Han Xie; Y.C. Lin; Xin-Tao Yan; Zhengbing Xu; Gang Xiao (Journal of Materials Research and Technology, 2023)
High-temperature flow features of the Al−Zn−Mg−Cu−Zr aluminum alloy was revealed by hot compression tests. The evolution mechanisms of dislocation clusters, subgrain, and dynamic recrystallization (DRX) grains, are thoroughly explored by EBSD and TEM analysis. Experimental results suggest that the high strain rate can exacerbate dislocation clusters formation, as well as subgrain nucleation/accumulation, inducing the increasing of flow stress. Nevertheless, the noticeable annihilation of substructures, as well as the growth of DRX grains, emerge at the higher temperature, causing the descending of flow stress. Three types of DRX nucleating mechanisms, i.e., discontinuous DRX (DDRX), geometric DRX (GDRX) and continuous DRX (CDRX) are activated in the Al−Zn−Mg−Cu−Zr aluminum alloy during hot compression. Simultaneously, the GDRX often appears at a high compressed temperature or a low strain rate. A physically-based (PB) model is proposed to collaboratively reconstruct true stresses and microstructure evolution features. The estimated values of true stress, DRX fractions and average grain size preferably fit the experimental data, indicating the proposed PB model can precisely catch the thermal compression behaviors and microstructure evolution characteristics of the Al−Zn−Mg−Cu−Zr aluminum alloy.